2020
DOI: 10.1155/2020/2679539
|View full text |Cite
|
Sign up to set email alerts
|

CHA2DS2-VASc Score as a Predictor for Left Atrial Thrombus or Spontaneous Echo Contrast in Patients with Nonvalvular Atrial Fibrillation: A Meta-Analysis

Abstract: Objective. This meta-analysis aimed at exploring the predictive value of CHA2DS2-VASc score for the left atrial thrombus (LAT) or left atrial spontaneous echo contrast (LASEC) in patients with nonvalvular atrial fibrillation (NVAF). Methods. PubMed, Embase, Web of Science, ScienceDirect, Cochrane Library, and Chinese core journals of the CNKI and Wanfang databases were searched to identify all the relevant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
1
1
4
Order By: Relevance
“…The CHA 2 DS 2 -VASc score has been reported to be predictive of SEC presence, 13 nevertheless, it was not a risk factor for SEC severity in our study. It is noteworthy that the CHA 2 DS 2 -VASc score system is applied to the general population, while our study focused on the subgroup of NVAF patients with SEC, and compared the characteristics of patients with different severity of SEC.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The CHA 2 DS 2 -VASc score has been reported to be predictive of SEC presence, 13 nevertheless, it was not a risk factor for SEC severity in our study. It is noteworthy that the CHA 2 DS 2 -VASc score system is applied to the general population, while our study focused on the subgroup of NVAF patients with SEC, and compared the characteristics of patients with different severity of SEC.…”
Section: Discussioncontrasting
confidence: 77%
“…11 Previous studies have identified several risk factors for SEC presence in NVAF patients, such as the medical history of heart failure (HF), presence of mitral regurgitation (MR), dilated LA, fibrinogen, and the CHA 2 DS 2 -VASc score. 6 12 13 14 However, it remains unclear if these risk factors could impact the severity of SEC and further affect the ischemic risk of NVAF. Moreover, there remain very limited data on the impact of different SEC densities on the ischemic stroke risk of NVAF patients after radiofrequency catheter ablation (RFCA).…”
Section: Introductionmentioning
confidence: 99%
“…На шансы выявления тромба в УЛП у больных с ФП оказывает влияние и клиническая оценка риска инсульта [7,8]. По нашим данным, высокий риск инсульта повышает шансы тромбоза УЛП в 2,90 (1,84-4,56) раза как у больных, получающих адекватную АКТ, так и у больных такой терапии не получающих.…”
Section: Discussionunclassified
“…Кардиоваскулярная терапия и профилактика. 2021;20 (7):2783. doi:10.15829/1728-8800-2021-2783 ISSN 1728-8800 (Print) ISSN 2619-0125 (Online) О возможности использования оценки риска инсульта у больных с персистирующей фибрилляцией предсердий для решения вопроса о целесообразности проведения чреспищеводной эхокардиографии перед кардиоверсией Мазур Е. С., Мазур В. В., Баженов Н. Д., Орлов Ю. А.…”
unclassified
“…Поиску предикторов предсердного тромбоза у больных персистирующей ФП посвящены многочисленные исследования, выявившие связь предсердного тромбообразования с разнообразными факторами, начиная от группы крови и заканчивая морфологическим особенностями УЛП [3][4][5]. Особенно активно изучается возможность использования для прогнозирования вероятности предсердного тромбоза оценки риска инсульта по шкале CHA 2 DS 2 -VASc (Congestive heart failure, Hypertension, Age, Diabetes mellitus, Stroke, Vascular disease, Age, Sex category) [6]. Однако такая оценка не обеспечивает достаточной точности прогнозирования предсердного тромбоза [6], что побуждает одних исследователей модифицировать эту шкалу за счет добавления дополнительных предикторов [7][8][9], а других -разрабатывать собственные прогностические шкалы [10].…”
Section: Introductionunclassified